2000
DOI: 10.1074/jbc.c000056200
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Cystathionine β-Synthase Is a Pyridoxal Phosphate Enzyme but, Unlike the Human Enzyme, Is Not a Heme Protein

Abstract: Our studies of cystathionine ␤-synthase from Saccharomyces cerevisiae (yeast) are aimed at (1) clarifying the cofactor dependence and catalytic mechanism and (2) obtaining a system for future investigations of the effects of mutations that cause human disease (homocystinuria or coronary heart disease). We report methods that yielded high expression of the yeast gene in Escherichia coli and of purified yeast cystathionine ␤-synthase. The absorption and circular dichroism spectra of the homogeneous enzyme were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
138
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(143 citation statements)
references
References 38 publications
5
138
0
Order By: Relevance
“…The absorption spectrum of rTcCBS exhibited major peaks at 280 and 410 nm in a ratio of 1:0.16, typical of a pyridoxal phosphate-containing enzyme (43). However, no peak was visible around 428 nm, which was indicative of heme in case of rat and human CBS (43). Removal of the pyridoxal phosphate resulted in an apoenzyme having no absorbance in the visible range (data not shown).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The absorption spectrum of rTcCBS exhibited major peaks at 280 and 410 nm in a ratio of 1:0.16, typical of a pyridoxal phosphate-containing enzyme (43). However, no peak was visible around 428 nm, which was indicative of heme in case of rat and human CBS (43). Removal of the pyridoxal phosphate resulted in an apoenzyme having no absorbance in the visible range (data not shown).…”
Section: Resultsmentioning
confidence: 95%
“…Unlike human CBS, rTc-CBS was not activated by the presence of 1 mM S-adenosylmethionine and did not contain detectable amounts of heme (data not shown). The absorption spectrum of rTcCBS exhibited major peaks at 280 and 410 nm in a ratio of 1:0.16, typical of a pyridoxal phosphate-containing enzyme (43). However, no peak was visible around 428 nm, which was indicative of heme in case of rat and human CBS (43).…”
Section: Resultsmentioning
confidence: 96%
“…The function of this ligand is yet to be determined; however, several laboratories have shown that it is not directly involved in the catalytic process [8][9][10][11], thus contradicting previous reports that have shown catalytic involvement [12,13]. CBS from lower eukaryotes such as Saccharomyces cerevisiae do not contain heme [8,9]. Thus the absence of this cofactor in CBS from lower eukaryotes suggests that the function of heme in this enzyme is unique to higher organisms.…”
mentioning
confidence: 79%
“…In vitro enzyme reaction and TLC The CBS enzyme activity was determined by modification of previously reported methods (Jhee et al 2000;Shan and Kruger 1998). A total of 50 ll of reaction volume contained 5 ll of 1-M Tris-HCl (pH 8.6), 2.5 ll of 5-mM PLP, 2.5 ll of 10 mg/dl BSA, 5 ll of 10-mM cystathionine, 1 ll of 14 C-serine, 1 ll of 50-mM AdoMet, 165 lg of calibrated CBS protein for the NIH3T3 cell line, and 80 lg of calibrated CBS protein for the COS7 cell line.…”
Section: Cell Harvest and Protein Extractionmentioning
confidence: 99%